WAYS TO DEVELOP DIGITAL COMPETENCE IN STUDENTS THROUGH LOCAL TECHNOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Digital skills are becoming increasingly important in almost every industry, and employers are looking for candidates with these skills. By incorporating local-module technologies into the curriculum, students can gain hands-on experience and develop the digital skills they need to succeed in their careers. Additionally, by continually reviewing and improving the use of these technologies, higher education institutions can ensure that their students are updated with the latest trends and technologies in their fields.